(untitled) (Quinto Sol, 2013)
Return to the polls and electoral triumph of Peronism in 1973 closed a stage characterized by a deep legitimacy crisis, which had been opened with Perón overthrow in 1955. The political reorganization of the “movement”vin the province of Mendoza showed an intermittent tension between those who adhered to the “verticalist peronism” and a group of leaders who built new political parties called “neo-Peronist”, whose rise found an end in 1966 gubernatorial elections. Rehabilitation of political activity in 1971 revived the internal fighting among the various Peronist factions, looking for a place in the nominations process for the 1973 elections. Despite the unification of some sectors, the conflict within the party did not end after the victory at the polls, but surfaced soon after the start of the Government of Alberto Martinez Baca. The purpose of this paper is to analyze the decomposition process that Peronism of Mendoza 1suffered after the overthrow of Perón in 1955, its subsequent reorganization to face the general elections of 1973 and the results of the elections.